Undeclared animal species in dry and wet novel and hydrolyzed protein diets for dogs and cats detected by microarray analysis - Rebecca Ricci; Daniele Conficoni; Giada Morelli; Carmen Losasso; Leonardo Alberghini; Valerio Giaccone; Antonia Ricci; Igino Andrighetto (BMC Veterinary Research, 2018)
Abstract Background Although the European Pet Food Industry Federation (FEDIAF) stated that labels must be accurate and provide detailed information on the ingredients, mislabeling of pet food has been documented by several authors. This phenomenon is of particular concern when related to products used as elimination diets for the diagnosis of adverse food reaction (AFR) in dogs and cats because the presence of undeclared ingredients may negatively interfere with the trial and prevent the veterinarian from making an appropriate diagnosis. The aim of this study was to shed light upon the problem of contamination and mislabeling in both dry and wet novel protein diets (NPDs) and hydrolyzed protein diets (HPDs) using a microarray-based commercial kit which tests for the presence of 19 animal species. Results Of the 40 analyzed products (9 dry NPDs, 22 wet NPDs, 6 dry HPDs and 3 wet HPDs), ten presented a content that correctly matched the label, while five did not contain the declared animal species, twenty-three revealed the presence of undeclared animal species, and two had a vague label that did not allow the evaluation of its accuracy. The most frequently contaminants identified in both dry and wet pet foods were pork, chicken and turkey. The presence of undeclared animal species was higher in dry than wet pet foods; furthermore, a lower number of contaminating animal species was identified in HPDs than NPDs (4 vs 10), and a lower number of contaminated HPDs (6 out of 9, 67%) than contaminated NPDs was detected (24 out of 31, 77%). Thirteen out of 14 brands tested presented at least one mislabeled product. Conclusions Mislabeling seems to be a widespread issue in pet foods used as elimination diets. Contamination can occur in all types of products used for the purpose, although dry NPDs are the main issue. Due to the high risk of contamination, particular attention should be given to both the selection of raw material suppliers and the production process.